Possible implication of NFKB1A and NKG2D genes in susceptibility to HTLV-1-associated myelopathy/tropical spastic paraparesis in Peruvian patients infected with HTLV-1 - Talledo, Michael; López, Giovanni; Huyghe, Jeroen R.; Verdonck, Kristien; González, Elsa; Clark, Daniel; Vanham, Guido; Gotuzzo, Eduardo; Van Camp, Guy; Van Laer, Lut (Journal of medical virology, 2012)
The human T‐cell lymphotropic virus type 1 (HTLV‐1) is the etiological agent of HTLV‐1‐associated myelopathy/tropical spastic paraparesis (HAM/TSP), a progressive disease causing paraparesis of the lower limbs. Only a minority of persons infected with HTLV‐1 develop HAM/TSP. Universal susceptibility factors for HAM/TSP are not known. The viral genotype is similar in asymptomatic carriers and HAM/TSP patients. High proviral load has been associated consistently with HAM/TSP, but this factor does not explain fully the presence of disease in HTLV‐1‐infected subjects. Most likely, host genetic factors will play an important role in HAM/TSP development. A two‐stage case‐control study was carried out to evaluate the association between HAM/TSP and candidate single nucleotide polymorphisms (SNPs) from 45 genes in addition to six human leukocyte antigen (HLA) alleles. Ancestry‐informative markers were used to correct for population stratification. Several SNPs belonging to NFKB1A and NKG2D showed a trend of association in both stages. The fact that the direction of the association observed in the first stage was the same in the second stage suggests that NFKB1A and NKG2D may be implicated in the development of HAM/TSP. Further replication studies in independent HTLV‐1 patient groups should validate further these associations. J. Med. Virol. 84:319–326, 2012. © 2011 Wiley Periodicals, Inc.